Design of an end-user centric information interface from data-rich performance analysis tools in elite swimming - Mullane, S. L.; Justham, L. M.; West, A. A.; Conway, P. P. (Procedia Engineering, 2010)
The acceptance of novel performance analysis tools in any sporting domain is heavily dependent on the perceived effectiveness determined by the user type. The extent to which these varied needs can be captured and the flexibility within a systems design is investigated within the research presented in this paper through the application of conceptual enterprise models based upon the Computer Integrated Manufacturing Open System Architecture (CIMOSA) modelling framework. The CIMOSA cube has been used to accommodate a generic design that can be adapted into a swimming specific model, the aim being to develop Human Machine Interfaces (HMI's) that can be simplified, scaled and reused within numerous sporting domains by formally modelling stakeholder requirements.